2022
DOI: 10.1039/d1ja00293g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of intensity ratios of Nd, Cs, Zr and Sr against U and burn-up in simulated nuclear fuels by LA-ICPMS

Abstract: Laser ablation coupled to inductively coupled plasma mass spectrometry (LA-ICPMS) is employed in spatial profiling mode to determine isotopic ratios and burn-up of simulated fast breeder reactor (FBR) fuel containing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…From literature reports 19 and our earlier experimental studies, 10 TBP is found to enhance the ionization efficiency and it is known that the formation of a metal complex having a nitrate counter ion is favoured in a methanol medium. 2 Graphite has high absorption capacity for laser radiation. Rapid heat generation from the absorbed laser energy leads to desorption/ionisation, which improves ionisation efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From literature reports 19 and our earlier experimental studies, 10 TBP is found to enhance the ionization efficiency and it is known that the formation of a metal complex having a nitrate counter ion is favoured in a methanol medium. 2 Graphite has high absorption capacity for laser radiation. Rapid heat generation from the absorbed laser energy leads to desorption/ionisation, which improves ionisation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Samples in the form of solution were analyzed by LIBS and LIMS, whereas three different sampling methods, e.g. , direct solution, 5,10 pulsed laser deposition of solid samples followed by dissolution 11 and direct laser ablation of solid samples, 2 were employed for MC-ICPMS. Heavy elements and burn-up monitors can also be quantified using ID MC-ICPMS like ID-TIMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation